176: YAP/TAZ ACTIVATION IS A MECHANISM OF TUMOR PROGRESSION IN THE POORLY COHESIVE GASTRIC CANCER PHENOTYPE. (23rd April 2022) - Sacco, M; Bencivenga, M; Torroni, L; Tomezzoli, A; Castelli, C; Alloggio, M; Verlato, G; Giacopuzzi, S; Iglesias, M; Pera, M; De Manzoni, G; Melisi, D
Abstract: Background and aim: Poorly Cohesive Gastric Cancer (PC-GC), according with the latest WHO classification, has a poor prognosis and its relative incidence is increasing. Disregulation of the Hippo pathway and/or activation of YAP/TAZ signaling pathway are emerging as central determinants for tumor initiation, progression and chemoresistance. The role of YAP/TAZ in human GC has not been defined to date. We hypothesized that RhoA-YAP/TAZ axis is a mechanisms of tumor progression in PC-GC, influencing prognosis. Methods: We retrospectively analysed 131 PC-GC patients, treated at two European surgical centres from 2004 to 2014. YAP/TAZ nuclear expression was analysed with immunohistochemistry. Both YAP and TAZ nuclear expression was coded as 'negative' (complete absence of nuclear reactivity) or 'any positive' (both low and high nuclear expression). Results: 21 patients showed absence of nuclear reactivity YAP−/TAZ-, while 110 showed any positivity: YAP+ (85/133 = 63.9%), TAZ+ (93/131 = 69.9%). Pathological tumor stage were significantly earlier in YAP−/TAZ- patients; 38% of YAP−/TAZ- were pT1–2 compared with only 17% of cases showing any expression ( P  = 0.041). Patients without nuclear YAP/TAZ expression were pN0 in 55% of cases compared with 26% of cases with any positive nuclear reaction ( P  = 0.020). In negative group 5-year OS was 57% compared with 29% in any positive group ( P  = 0.030). 5-year survival was the highest in YAP−/TAZ- group, intermediate when only one of the two biomarkers was expressed, and the lowest in YAP+/TAZ+ group ( P  = 0.010). Conclusion: Nuclear negativity to both YAP and TAZ identify a subgroup of PC-GC with more favourable prognosis. Higher clinic-pathological stage and a worse OS was associated to YAP/TAZ positive patients supporting the involvement of this pathway in the progression of PC gastric carcinoma. Our results provide new insights into the role of YAP/TAZ signalling cascade as a mechanism of cancer progression in sporadic PC-GC.